Transferencias por canon y sobrecanon petrolero y su relación con el crecimiento económico de la región Loreto en el periodo 2012-2022 - Villacis Lozano, Janira Dayane (2024)
The analysis of the oil canon and overcanon in the Loreto region during 2012 2022 reveals a weak positive correlation (r=0.264575) between these incomes and regional economic growth, indicating that variations in the canon are closely linked to economic fluctuations. With a coefficient of determination (R2 = 0.0700), it is observed that a weak positive variability in economic growth can be explained by the income from the canon and overcanon, highlighting its not very significant impact. There is no significant correlation. This result underlines the importance of the oil fee in regional development, but also points out the need to identify and manage other elements that affect the local economy to achieve sustained growth.